2016
DOI: 10.1002/14651858.cd006425.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal breastfeeding education for increasing breastfeeding duration

Abstract: There was no conclusive evidence supporting any antenatal BF education for improving initiation of BF, proportion of women giving any BF or exclusively BF at three or six months or the duration of BF. There is an urgent need to conduct a high-quality, randomised controlled study to evaluate the effectiveness and adverse effects of antenatal BF education, especially in low- and middle-income countries. Evidence in this review is primarily relevant to high-income settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 119 publications
5
69
1
3
Order By: Relevance
“…It is interesting to note that our participants who achieved six months of EBF had, in addition to more overall contacts with IBCLCs, better baseline breastfeeding knowledge than those who stopped earlier. This finding is in agreement with previous literature in which the combination of breastfeeding education and professional lactation support was reported to improve six-month EBF more than breastfeeding education alone (OR = 2.50; 95% CI: 1.00 to 6.25) [11,12]. We hypothesize that participants with better baseline breastfeeding knowledge were more enthusiastic about breastfeeding, which may have motivated them to seek further knowledge by attending the antenatal breastfeeding educational session designed for the trial participants allocated to the experimental group.…”
Section: Discussionsupporting
confidence: 93%
“…It is interesting to note that our participants who achieved six months of EBF had, in addition to more overall contacts with IBCLCs, better baseline breastfeeding knowledge than those who stopped earlier. This finding is in agreement with previous literature in which the combination of breastfeeding education and professional lactation support was reported to improve six-month EBF more than breastfeeding education alone (OR = 2.50; 95% CI: 1.00 to 6.25) [11,12]. We hypothesize that participants with better baseline breastfeeding knowledge were more enthusiastic about breastfeeding, which may have motivated them to seek further knowledge by attending the antenatal breastfeeding educational session designed for the trial participants allocated to the experimental group.…”
Section: Discussionsupporting
confidence: 93%
“…The evidence of health benefits from healthy diets through the life-course warrants its recommendation during pregnancy, while recognizing the importance of addressing social determinants. Similarly, individual-focused education efforts to promote breastfeeding have small effects ( 92 , 93 ), highlighting the importance of social determinants of breastfeeding. Systematic reviews have documented that interventions for parent feeding practices ( 94 ) and child diet ( 94 , 95 ) have promise.…”
Section: Implications and Recommendations For Nutrition Policy And Prmentioning
confidence: 99%
“…In a recent systematic review (September 2012), results from 13 studies showed that in order to select the best learning approach for breastfeeding, clinical trials should be done (12). Face to face and small group learning approaches are two common methods in breastfeeding promotion programs and there is no study to compare these two methods.…”
Section: Self-efficacymentioning
confidence: 99%